2010
DOI: 10.1111/j.1530-0277.2010.01349.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased Oxidative DNA Damage in Patients With Alcohol Dependence and Its Correlation With Alcohol Withdrawal Severity

Abstract: These results indicate that our alcohol-dependent individuals are vulnerable to excessive production of free radicals. Notably, the oxidative DNA damage persisted after 1-week detoxification. The AWS severity was correlated with the increase in oxidative stress, particularly the 8-OHdG levels. The impact of sustained abstinence in alcoholic patients needs to be investigated in future studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
1
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 61 publications
(67 reference statements)
1
32
1
3
Order By: Relevance
“…This finding suggests that a heightened oxidative DNA damage would not recover during early alcohol withdrawal. 46 …”
Section: Enhanced Oxidative Dna Damage Following Chronic Alcohol Consmentioning
confidence: 97%
See 1 more Smart Citation
“…This finding suggests that a heightened oxidative DNA damage would not recover during early alcohol withdrawal. 46 …”
Section: Enhanced Oxidative Dna Damage Following Chronic Alcohol Consmentioning
confidence: 97%
“…40 We found that AWS severity is correlated more robustly with 8-OHdG and MDA levels. 46 The phenomenon suggests that AWS, a manifestation of central glutamate overexcitation, is interwoven with oxidative damage which presumably contributes to mechanisms of addiction.…”
Section: Oxidative Stress Contributes To Alcohol Withdrawal and Addicmentioning
confidence: 99%
“…Chronic alcohol consumption by humans and oxidative DNA damage has been correlated with withdrawal symptoms (Chen et al 2011). However, to the best of our knowledge, there is little information regarding the functional association between biochemical changes in ADE and the acquisition of alcohol dependence with respect to brain cell DNA toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Y. Yeh et al, 2007). Chronic alcohol exposure’s relationship to oxidative stress in the systemic circulation (Burnham et al, 2012; Yang et al, 2010), liver (C. H. Chen, Pan, Chen, & Huang, 2011; Leung & Nieto, 2013; Sid, Verrax, & Calderon, 2013), gut (Abdelmegeed et al, 2013; Keshavarzian et al, 2009; S.…”
Section: Introductionmentioning
confidence: 99%